Characteristics of Cognitive in Children with Learning Difficulties - Liang, Feng (Transl Neurosci, 2019)
In order to explore the relationship between cognitive function in children with learning difficulties and social environment, this study uses the Wechsler Intelligence Scale and the self-made general environment questionnaire to investigate 185 children with learning difficulties and compares them with 185 normal children, and gives attention test to 50 children with learning difficulties. The results show that family environment has a certain influence on the children with learning difficulties, they have a significantly lower verbal intelligence quotient (VIQ), performance intelligence quotient (PIQ) and full scale intelligence quotient (FIQ), and the separation of VIQ and P IQ is common among them. As the children with learning difficulties grow older, their ability for abstract generalization tends to decline, which may be a characteristic of their intelligence development. This study aims to compare the functional differences in cortical regions between children with learning difficulties and children without from the perspective of cognitive neuropsychology, so as to provide effective assistance for children with learning difficulties.